Simulating Dynamic Systems Using Linear Time Calculus Theories. Issue 4 (21st July 2014) - BOGAERTS, BART; JANSEN, JOACHIM; BRUYNOOGHE, MAURICE; DE CAT, BROES; VENNEKENS, JOOST; DENECKER, MARC; Leuschel, Michael; Schrijvers, Tom
Abstract Dynamic systems play a central role in fields such as planning, verification, and databases. Fragmented throughout these fields, we find a multitude of languages to formally specify dynamic systems and a multitude of systems to reason on such specifications. Often, such systems are bound to one specific language and one specific inference task. It is troublesome that performing several inference tasks on the same knowledge requires translations of your specification to other languages. In this paper we study whether it is possible to perform a broad set of well-studied inference tasks on one specification. More concretely, we extend IDP3 with several inferences from fields concerned with dynamic specifications.